Varicocele: Acute Complications of a Chronic Disease (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Depending on the degree of varicocele, treatment can be conservative or operative. If severe pain occurs as a result of thrombosis, phlebitis and rupture of the pampiniform plexus veins with the formation of a scrotal hematoma, surgical intervention must be performed urgently. Sometimes, with technical errors during surgery for iatrogenic varicocele (ligation or transection of the ureter, failure of ligatures on the vein stump), patients need emergency help. In case of urgent complications of varicocele due to its late diagnosis, patients also need emergency or urgent surgical care. These aspects of the problem in the urological literature are poorly covered and, therefore, practical urologists are almost not aware of them, therefore they are almost never diagnosed or under the auspices of other emergency testicular diseases (acute orchitis, epididymitis, testicular torsion, acute scrotum).